Does money supply growth cause inflation in the West African Monetary Zone? - Hassan O. Ozekhome (West African Journal of Monetary and Economic Integration, 2017)
Anecdotal evidence shows that monetary expansion (excess liquidity) induces inflation in the West African Monetary Zone (Zone). Uncertainty about the nature of inflation persistence often undermines regional convergence due to the asymmetric responses from the monetary authorities. It is against this background that this paper sought to examine the dynamics of money supply growth and inflation in the WAMZ countries, using panel data methodology for the period 2000-2015. The empirical results show that monetary expansion, exchange rate depreciation, oil price, fiscal deficits and lagged inflation (proxy for previous inflation) are the principal drivers of inflation in the WAMZ countries; an evidence of monetary and structural-induced inflation in the sub-region. Real output growth on the other hand, is found to reduce inflation in the sub-region. We recommend amongst others; the curtailment of excessive monetary expansion in order to tame domestic inflationary pressures, adoption of sound and prudent fiscal expenditure, coherent and stable macroeconomic policies in terms of exchange rate and interest rates, increase output capacity, and policy coordination and harmonisation with respect to inflation control, in order to achieve low inflation rate relevant for monetary and economic integration.
Keywords: E51; E52; C13; 330; Money supply growth; Inflation; Macroeconomic convergence; WAMZ; Panel data